FROM SOCIAL VULNERABILITY TO POLITICAL VULNERABILITY (Revista Paradigma, 2022)
In the context of a democracy, contrary to authoritarian and totalitarian regimes, citizens acquire a decisive role in making political decisions. In the opportunity for deliberation, demands are raised and democratic participation takes on meaning. However, not everyone is able to conquer space in the arenas of public discussions, which is why the demands of certain excluded and marginalized groups are not discussed at all and, consequently, need to be addressed. One of the considerable causes of the difficulty of access of certain groups to the places of deliberation is social inequality. Investigating the impacts of inequality on society is a challenging task, not because the related problems are difficult to verify, but because it is costly to find mechanisms that can act to mitigate inequalities and curb their reflexes in the various spheres of social construction. In this logic, the study proposes an analysis, based on the deductive research method, which runs through the dilemmas of contemporary democracy, and which develops from the intertwining between political equality and social inequality, in order to investigate whether the existence of a regime democratic political system is sufficient to guarantee political equality. In final notes, he concludes that the absence of socioeconomic inequality is a condition that precedes substantive political equality.